Biodiversity of Leaf Litter Arthropods in Alnaser Forest, Tripoli, Libya. (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
Monthly results using Berlese funnels showed differences in population density of micro-fauna associated with Eucalyptus camaldulensis, Pinus halepensis and the climatic factors at Al Naser forest, Tripoli for a total of 120 samples of leaf litter 2009. Total annual of micro-fauna density was 119,770 individuals /15 cm / m³ thickness of leaf litter. Results revealed that population number of collembola was effective in disintegrating and breaking leaf litter, mites as predators, fungi, and bacteria leaf litter breaking down. The study was divided into two periods. (1)  May - October, showed mean abundance of mites was 24.8, collembola 42, and the other micro-fauna 100 individuals /15 cm /m³ thickness of leaf litter respectively. (2) November - April, showed mean abundance of mites was 95, collembola 135, and the other micro-fauna group 100 individuals /15 cm/ m³ thickness of leaf litter respectively. Significant differences were found at the 0.001 level and in Duncan test at 0.001 level between January and other months. All the data biological, chemical and physical factors affecting biodiversity of arthropods leaf litter of eucalyptus and pine in Al-Nasr Forest in Tripoli were presented. The study recommends considering the importance of identifying, classifying, and biological diversity of micro-fauna associated with leaf litter as important environmental indicators and sustainability of the forest ecosystem in Libya.
Keywords: Forest; Collembolan; Mites; Conifers; Camphor; Biodiversity; Libya